Síntese de Novos Nucleosídeos Quinolônicos não Naturais como Potenciais Agentes Antivirais - Gomes, Claudia Regina Brandão (2003)
The interesting biological activities of synthetic quinoline derivatives as antibacterial and antiviral agents urged many research groups to construct numerous analogues of such compounds. Since the discovery of acyclovir as a potent and selective antiherpes virus agent, considerable interest has been focused in the synthesis of novel acyclonucleoside analogues in the search for more effective, selective and non toxic antiviral our antitumor agents. In this study 23 new quinolonic acyclovir analogues were synthesized: 1-[(2-hydroxyethoxy)methyl]-3-carbethoxy-4(1H)quinolone (80a-m) and 1-[(2-hydroxy-ethoxy)methyl]-4(1H)quinolone-3-carboxilic acid (81a-j,m). The quinolones were previously synthesized by known procedures. For preparing the quinolone acyclovir analogues in good yields, we introduced some modifications which significantly improved the previous described procedure of Ubasawa et all in terms of simplicity and yields. Thus, our route towards compounds type 80, employed a one pot reaction: silylation of the desired quinolone (BSTFA1%TMCS) followed by equimolar amount addition of 1,3-dioxolane, chlorotrimethylsilane and KI, at room temperature. The acyclonucleosides 80 a-m were obtained in 40-77% yields. The esthers 80 compounds were subsequently converted into the corresponding hydroxyacids: 1-[(2-hydroxy-ethoxy)methyl]-4(1H)quinolone-3-carboxilic acid (81a-j,m) in 40-70% yields. Antiviral activity of 80 and 81 on HSV-1 virus infection was assessed by virus yield assay. The carboxylic acids 81 and the esthers 80, except compounds 80g and 81g were found to reduce the virus yield in 93 to 99% at the concentration of 50 M, being the acids, in general, more effective inhibitors than their corresponding esthers. Attempts of tosylation reaction of 1-[(2-hydroxy-ethoxy)methyl]-6-methyl-3-carbethoxy-4(1H)quinolone (80a) using tosyl chloride in pyridine or p-toluenesulfonic acid, K10 failed to give the desired derivative. Reaction of 1-[(2-hydroxy-ethoxy)methyl]-6-methyl-3-carbethoxy-4(1H)quinolone (80a) with diisopropyl phosphonate chloride (92) didn t lead to the phosphate (84a) products, probably due to starting materials decomposition during the reactions. Aiming towards quinolonole seco-nucleosides, ribonucleosides 6-methyl-1-(2,3,5-tri-O-benzoyl--D-ribofuranosyl-4(1H)quinolone-3-carboethoxy (69a) was prepared by known procedures developed by our group. Compound 69a treated with NaIO4 and NaBH4 supported in resin amberlist A-21 failed to give any nucleoside product. In this study, we also applied a new methodology aiming towards 2`,3`-didehydro-2`,3`-dideoxyribonucleosides (73a). The 6-methyl-1-(-D-ribofuranosyl-4(1H)quinolone-3-carbomethoxy (93a) was transformed into 6-methyl-1-(2´,5´-di-O-acetyl-3´-bromo-3´-deoxy--D-ribofuranosyl-4(1H)quinolone-3-carbomethoxy (78a) and 6-methyl-1-(3´,5´-di-O-acetyl-2´-bromo-2´-deoxy--D-ribofuranosyl-4(1H)quinolone-3-carbomethoxy (78a´) on application of Isawa procedure. This bromoacetate product mixture was reacted with. NiCl2(PPh3)2 or Ni(acac)2. It is noteworthy that under these conditions the glycosidic bond uderwent cleavage.